Sustainable consumption through policy intervention—A review of research themes - Mont, Oksana; Lehner, Matthias; Dalhammar, Carl (Frontiers in Sustainability, 2022)
Policy-makers are starting to acknowledge the urgent need for policy-intervention to achieve sustainable consumption. However, it is difficult to achieve policy-making that leads to impactful consumption interventions. Generally speaking, sustainable consumption can be achieved in three ways; to reduce consumption, to change consumption, and to improve consumption. These strategies all have their advantages and disadvantages regarding the likelihood for impactful policies to be implemented. Prior research identifies policies with big impact potential for all three of these strategies, but also clearly shows that none of the three strategies has so far been successfully applied to achieve sustainable consumption. Indeed, success remains elusive in each of the strategies to adopt the most impactful policies available due to limited implementability. The goal of this article is to provide a broad overview of research on sustainable consumption and to discuss future directions for research.